2015
DOI: 10.1186/s12885-015-1186-0
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib inhibits intracellular signaling pathways and induces cell cycle arrest and cell death in thyroid carcinoma cells irrespective of histological origin or BRAF mutational status

Abstract: BackgroundPatients with dedifferentiated or anaplastic thyroid carcinomas currently lack appropriate treatment options. Kinase inhibitors are among the most promising new agents as alternative strategies. The BRAF- and multi-kinase inhibitor, sorafenib, has already shown antitumor effects in thyroid carcinoma patients in a phase III clinical trial. In this study we aim to better characterize molecular effects and efficacy of sorafenib against thyroid carcinoma cells with various histological origins and differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
37
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 60 publications
6
37
0
2
Order By: Relevance
“…As far as the mechanisms of action in MPM TICs, sorafenib treatment for 24–48 h induces G1 cell cycle arrest, as also reported in NSCLC [49] or thyroid cancer cell lines [50]. Interestingly, in our experimental model, cell death was mostly observed after 72 h of treatment, indicating that sorafenib inhibition of MPM TIC proliferation precedes the activation of the apoptotic process.…”
Section: Discussionsupporting
confidence: 80%
“…As far as the mechanisms of action in MPM TICs, sorafenib treatment for 24–48 h induces G1 cell cycle arrest, as also reported in NSCLC [49] or thyroid cancer cell lines [50]. Interestingly, in our experimental model, cell death was mostly observed after 72 h of treatment, indicating that sorafenib inhibition of MPM TIC proliferation precedes the activation of the apoptotic process.…”
Section: Discussionsupporting
confidence: 80%
“…Second, we observed a growth-inhibitory effect and an arrest in the S-phase of the cell cycle as the mode of the cytotoxic action of sorafenib, which has been previously described in papillary thyroid carcinoma cell lines (BHT101, B-CPAP and TK1) and anaplastic cell lines (SW1736 and Hth7) [28]. Furthermore, in medulloblastoma, the effect of sorafenib in Daoy cells showed a decrease of cells in the G1-phase and an increase of cells arrested in the S-phase [29].…”
Section: Discussionmentioning
confidence: 52%
“…Forskolin decreased the expression level of the cell cycle modulator cyclin D1, while sorafenib decreased CDK4 and p-RB in the 3 examined cell lines. A previous report suggested that forskolin induces G1 phase arrest [14] although sorafenib affects the cell cycle differently depending on the cell lines [9]. We postulate that the cAMP pathway activated by forskolin directly inhibits progression through the G1 phase of the cell cycle, resulting in growth suppression of well-differentiated thyroid carcinoma cells.…”
Section: Discussionmentioning
confidence: 68%
“…proliferation and neovascularization by inhibiting both RTKs, such as RET, vascular endothelial growth factor (VEGF), and platelet-derived growth factor (PDGF), and their downstream signaling pathway, that is, the MAPK pathway [7][8][9][10][11]. Especially, sorafenib is a multikinase inhibitor that suppresses various types of RTKs and the following MAPK pathway [7,9].…”
mentioning
confidence: 99%
See 1 more Smart Citation